Child Sexual Crimes in Bali: A Criminological Review of Prevention and Policy - Roger Paulus Silalahi; Riska Sri Handayani; Vita Mayastinasari (Transpublika Publisher, 2026)
As one of Indonesia’s leading international tourism destinations, Bali faces increased interaction between visitors and vulnerable local communities, creating situational opportunities for exploitation. This research examines the persistence and dynamics of child sexual violence in Bali, with a particular focus on Child Sex Tourism (CST). Likewise, this study analyzes structural and situational factors contributing to child sexual crimes and evaluates institutional responses. Using a qualitative descriptive and documentary research design, the study integrates data from the Bali Regional Commission for Women and Child Protection (KPPAD), the Bali Office for Women and Child Empowerment (Dinas P3A), and the national SIMFONI PPA database for 2022–2024. The analysis follows the Miles and Huberman model of data reduction, display, and conclusion drawing. Findings show sexual violence accounts for about 40–45% of reported child violence cases, indicating a structural rather than incidental problem. Most victims are adolescent girls from low-income families working in tourism-related sectors, while offenders are typically adult males within the victims’ social environment. Although institutional mechanisms such as SAPA 129 and Village Protection Units exist, implementation remains fragmented, marked by low reporting rates and weak inter-agency coordination. By integrating Criminal Policy Theory and Routine Activity Theory, the study concludes that prevention requires both legal reform and community-based guardianship, including education, digital literacy, and tourism-sector monitoring. However, a gap persists between regulatory frameworks and enforcement, especially in informal tourism and online spaces, making current protection strategies largely reactive rather than preventive.